Controle químico de ninfas de libélula (Insecta, Odonata) durante a larvicultura do Jundiá (Rhamdia quelen) - Queiroz, Julio Cesar (2017)
The objective of this study was to verify the efficiency of the agrochemicals/ contaminants Methyl paration, Cypermethrin, Azadirachtin and Pyroligneous extract in the control of dragonfly naiads (P. flavescens) during the larviculture of the catfish (Rhamdia quelen) as well as to investigate the predation and the possible genotoxic, histopathological and neurotoxic damages that can cause in the larvae. Three trials were performed. In the first, different doses of each product were tested to determine lethal and lethargic doses. For this, 270 naiads were used for each product tested and 9 for control, totaling 1089 animals. The naiads were distributed in aquariums with a total volume of 1L in triplicates. To determine the doses, it started with an overdose (1000 μl / L-1) and then observed the time in which the naiads lead to death. The doses were gradually decreased in 100 μl and below that dose the decrease was in 5μl intervals. In the second trial, the doses determined in test I were used. Predation tests on product exposure were performed in aquaria with a total volume of 1L, arranged in triplicates for each test dose plus control. In each aquarium a nymph of dragonfly and 10 catfish larvae were arranged, observing the amount of larvae consumed in the lethal time of exposure to the product, as determined in the previous test. The design was completely randomized with nine treatments and three replicates, totaling 27 experimental units. The treatments were constituted by the doses of each product. In the third trial were carried out for 30 days the catfish larviculture with exposure to the products. 4000 catfish larvae were used with 120 hours post-hatching (HPE), randomly distributed in 20 tanks with a total volume of 70 l. The doses were applied at intervals of 7 days, simulating the egg laying cycle and hatching of the dragonfly nymphs. The water replacement was done daily at 5% along with cleaning the aquariums. The experimental design was completely randomized with five treatments and four replicates, totaling 20 experimental units. Eight lethal and lethargic doses were planned: 5 μl / L for Methyl paration, 10 μl / L for Cypermethrin, 30, 25 and 20 μl / L for Azadirachtin and 20, 15 and 10 μl / L for the Pyroligneous extract. In the predation tests, the treatment containing Azadirachtin at the doses of 30, 25 and 20 μl / L suggests survival of up to 43% of the larvae, Pyroligneous extract 25.6%, Cypermethrin and Methyl paration 87 and 73%, respectively. In the third trial after the larviculture were not evidenced any index of histopathological damage in liver and gills. The comet assay suggests that Cypermethrin and Methyl paration cause damage to DNA. The enzyme acetylcholinesterase was inhibited only by Methyl paration. The use of nim oil may be a natural alternative to use of agrochemicals in cultivation tanks in catfish larviculture (Rhamdia quelen), considering that it does not present toxicity to animals and predation is significantly reduced.